PERAN SUPERVISOR DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SD NEGERI LOGEDE KECAMATAN SUMBER KABUPATEN REMBANG - Ahmad Agus Alim; Mokhammad Arifin; Soedjono (STKIP Subang, 2025)
Education is a fundamental element in national development. High quality education not only plays a role in improving human resources but also becomes the basis for the progress of a country. The quality of learning at SD Negeri Logede also still requires serious attention. Teachers often face difficulties in preparing learning plans that are in accordance with student needs. In implementing learning, the methods used tend to be monotonous and less innovative, so that students are not actively involved in the learning process. This has an impact on student learning outcomes that are less than satisfactory. This study aims to analyze the role of supervisors in improving the quality of learning at SD Negeri Logede, Sumber District, Rembang Regency. The approach used is qualitative with a case study method. Data collection was carried out through interviews, observations, and documentation. The results of the study indicate that supervisors play an important role in academic supervision, teacher coaching, and curriculum development. The impact is seen in improving the quality of planning, implementation, and evaluation of learning. The obstacles faced by supervisors include limited time and resources. This study recommends strengthening collaboration between supervisors, teachers, and principals to create better quality learning. Keywords: supervisor, quality of learning, academic supervision